Circulating Tumor-Cell-Associated White Blood Cell Clusters in Peripheral Blood Indicate Poor Prognosis in Patients With Hepatocellular Carcinoma - Luo, Qiong; Wang, Chunming; Peng, Bangjian; Pu, Xiaoyu; Cai, Lei; Liao, Hangyu; Chen, Kunling; Zhang, Cheng; Cheng, Yuan; Pan, Mingxin (Frontiers in Oncology, 2020)
Aim: Circulating tumor cells (CTC) are a precursor to metastasis in several types of cancer and are occasionally found in the bloodstream in association with immune cells, such as white blood cells (WBCs). CTC-associated WBC (CTC-WBC) clusters can promote CTC appreciation and metastasis, suggesting that patients with CTC-WBC clusters found in the peripheral blood may have a worse prognosis. However, it is unclear whether CTC-WBC clusters are present in the peripheral blood of patients with hepatocellular carcinoma (HCC) and suggest a poor prognosis for HCC. Methods: We collected peripheral blood from 214 patients with HCC from January 2014 to December 2016. CanPatrol™ CTC analysis technology was used to isolate and count CTCs and CTC-WBC clusters in the patients' peripheral blood. Chi-squared analysis was used to calculate the correlation between the CTC-WBC clusters and clinicopathological characteristics. Kaplan–Meier survival analysis and Cox regression analysis were used to assess patient prognosis. Results: We used CanPatrol™ CTC analysis technology to count different types of CTCs and CTC-WBC clusters. The results showed that CTC-WBC clusters and tumor size (P = 0.001), tumor number (P = 0.005), portal vein tumor thrombus (P = 0.026), BCLC stage (P < 0.001), AFP level (P = 0.002), and total number of CTCs (P < 0.001) were statistically related. Cox regression analysis revealed that CTC-WBC clusters are an independent prognostic indicator of DFS (HR = 1.951, 95%CI:1.348–2.824, P < 0.001) and OS (HR = 3.026, 95%CI:1.906–4.802, P < 0.001) in HCC patients. Using Kaplan–Meier analysis, we found that positive CTC-WBC cluster patients had significantly shorter DFS and OS than patients with negative CTC-WBC (P < 0.001 and P < 0.001, respectively). Conclusions: CTC-WBC clusters in the peripheral blood are an independent predictor of DFS and OS, and their presence indicates poor prognosis in patients with HCC.